(untitled) (Revista Venezolana de Salud Pública, 2021)
This essay proposes that Medicine and Medical Education maintain ethical and practical theoretical debates that require adopting a interdisciplinary dialogical relationship for work together with other disciplines. This opening would allow to address complex social problems from different perspectives and ways of working. It is not a finished definitive product, they are organized and systematized ideas about possible and useful way to approach, know in depth, understand and resolve the complex reality we find in Medicine and Medical Education. Three mayor themes are presented: 1.The production of knowledge in Medicine: positivism paradigm, characteristics, challenges, new demands. 2. Reflective approach to different concepts of interdisciplinarity, various forms of integration of disciplines in the production of knowledge as a route of address complex problems that required new approaches and interrelations. 3. Interdisciplinarity and research: Characteristic of current research in Medicine, interdisciplinary research, contributions, challenges it faces and possible solutions. Finally reasons that justify the incorporation of interdisciplinarity in the production of knowledge in Medicine and the Medical Education of future prospects. If true interdisciplinarity is fulfilled in this respectful sharing between experts, each discipline will change its vision, language, beliefs, approaches and methods.